The Use of Canva Media to Improve Students’ Higher-Order Thinking Skills in Indonesian Language Learning - Sariningsih, Asih; H. Soro, Suharyanto (Dinasti Publisher, 2025)
This study aims to describe the use of Canva as an instructional medium in Indonesian language learning to enhance higher-order thinking skills among elementary school students. The research employed a qualitative approach with a case study design conducted at SDN Cengkareng Barat 05 Pagi and SDN Semanan 12 Pagi in West Jakarta. Data were collected through interviews, observations, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that teachers implemented the functions of instructional management comprehensively, including needs-based lesson planning, organizing learning tools and student groups, conducting visual-media-based instruction using Canva, and evaluating both processes and products through formative feedback and portfolio assessment. Canva was found to assist students in identifying key information, analyzing reading content, and creating visual representations that support the development of higher-order thinking skills. This study highlights that the success of integrating digital media depends on appropriate instructional design and instructional management, enabling the reinforcement of students’ visual literacy, creativity, and analytical abilities.